Family Interfere With Work Conflict: Dampaknya Pada Kepuasan Dalam Bekerja, Kinerja, Dan Niat Untuk Keluar Dari Pekerjaan - Prajogo, Wisnu (Jurnal Bisnis : Teori dan Implementasi, 2014)
This research examined the influence of family interfere with work conflict to job satisfaction, performance and intention to leave, and also the influence of job satisfaction to performance and intention to leave. Survey conducted on 128 bank employees found several findings. First, family interfere with work conflict has negative influence to job satisfaction. Second, job satisfaction has positive influence to performance. Third, job satisfaction has negative influence to intention to leave. Fourth, family interfere with work conflict has negative influence to job performance. Fifth, family interfere with work conflict has positive influence to intention to leave.